A case of internal beveling with an exit gunshot wound to the skull - Bhoopat T. (2014)
Exit gunshot wounds of the skull generally have external beveling while entrance wounds show internal beveling. With rare exceptions, entrance gunshot wounds show external beveling, usually of two types: the asymmetric 'keyhole' type and the symmetric 'non-keyhole' type. In exit gunshot wounds of the skull, only the keyhole type has been reported. This report shows that symmetric internal beveling from an exit gunshot wound to the skull may confuse medical personnel.